A forma do privilégio: renda, acessibilidade e densidade em Natal-RN - Carmo Júnior, João Batista (2014)
The aim of this work is to understand the morphological expression of ground occupation by the higher income population, by focusing on population distribution in accordance with income layers and demographical density, as well as topological accessibility (HILLIER and HANSON, 1984) resulting from the urban grid structure. It endeavors to identify a functional organizing principle regarding the intra-urban space of Natal capital city of the state of Rio Grande do Norte, the research focus. In order to achieve this, census data as well as syntactic data were utilized for mapping and spatial analysis of income patterns, topological accessibility and demographical density using Geographical Information System GIS. The organizing principle was named as the Form of Privilege, a pattern that concentrates or tends to concentrate wealth, topological accessibility and low demographical density. Attempting to assess its extent, beyond Natal, this principle was applied to other Brazilian northeastern capitals such as: Fortaleza, CE; Teresina, PI; Aracaju, SE; Recife, PE; and João Pessoa, PB. Findings point out that although the urban structures of these cities are not immune to the Form of Privilege, Natal is emblematic of this phenomenon, a fact that demonstrates the perverse character of its spatial process, which historically creates privileged areas within the city, by means of the appropriation of accessibility as well as of the many urban benesses that are related to it by higher income groups at the expense of the major part of the population, which though being the people mostly in need of the benefits originating from the urban form are excluded from them